EFFECT OF CRYOGENIC TEMPERING ON STEEL - Balasubramani, S.; Venkatesh, S.; Ramakrishnan, T.; Raja, S.Karthik; Sundaram, P.Shanmuga (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
In the field of mechanical engineering we are always looking to improve themechanical properties of the material. By doing so we can improve the quality of the product weare making. In order to improve the properties of the material, heat treatment process is used such that mechanical properties such as strength, hardness, wear resistance, etc. is improved. Butat the end of heat treatment we get material more brittle and difficult to use in practical.Tempering process is used to increase the ductility of material. Even though there will be someinternal stresses in the material, In order to remove these internal stresses and to improve the wear resistance of the material, new treatment called CRYOGENIC TEMPERING is used. Inthis project we have discussed about the effect of cryogenic tempering on steel.